Optimal Balanced Control for Call Centers - Sandjai Bhulai; Taoying Farenhorst-Yuan; Bernd Heidergott; Dinard van der Laan (Tinbergen Institute, 2010)
In this paper we study a challenging call center operation problem. The goal of our analysis is to identify an optimal policy for allocating tasks to agents. As a first step, we discuss promising randomized policies and use stochastic approximation for finding the optimal randomized policy when implemented via a Bernoulli scheme. As we will show in this paper, the performance of the call center can be improved if the randomized policy is implemented by a deterministic sequence satisfying some regularity conditions. Such sequences are called balanced and we will show that implementing randomized policies by balanced sequences provide an additional step in optimization and control. This motivates our new approach where we avoid the intermediate step of first finding an optimal randomized control and directly find the optimal balanced sequence for control of the call center via stochastic approximation.
Keywords: C61; C63; 330; Call Center; Measure-Valued Differentiation; Balanced Sequence; Optimization; Callcenter; Scheduling-Verfahren; Theorie